Cell-derived microparticles in haemostasis and vascular medicine - Burnier, Laurent; Fontana, Pierre; Kwak, Brenda R; Angelillo-Scherrer, Anne (Thrombosis and haemostasis, 2009)
Considerable interest for cell-derived microparticles has emerged, pointing out their essential role in haemostatic response and their potential as disease markers, but also their implication in a wide range of physiological and pathological processes. They derive from different cell types including platelets - the main source of microparticles - but also from red blood cells, leukocytes and endothelial cells, and they circulate in blood. Despite difficulties encountered in analyzing them and disparities of results obtained with a wide range of methods, microparticle generation processes are now better understood. However, a generally admitted definition of microparticles is currently lacking. For all these reasons we decided to review the literature regarding microparticles in their widest definition, including ectosomes and exosomes, and to focus mainly on their role in haemostasis and vascular medicine.